Metabolomic and chemometric profiling of crimson grapes during drying and its impact on antidiabetic activity - Doaa M. Abo-Atya; Doaa A. Ghareeb; Badr Aldahmash; Shaden A. M. Khalifa; Hesham R. El-Seedi; Eman Shawky; Dina S. Ghallab (npj Science of Food)
Abstract The present study investigates the metabolic profile and antidiabetic potential of Crimson Seedless grapes during the drying process using UPLC–QTOF-MS/MS and multivariate statistical analyses. A total of 50 metabolites were tentatively identified, including phenolic acids, flavonoids, stilbenes, anthocyanins, and lipids. Fresh grapes contain higher levels of glycosylated anthocyanins and stilbenes, while raisins exhibit an increased concentration of fatty acids and phosphatidylcholines. In vitro assays demonstrated potent α-amylase and α-glucosidase inhibitory activities of fresh grape extracts (IC50 = 157.5 ± 0.56 μg/mL and 91.89 ± 0.47 μg/mL, respectively), surpassing acarbose (positive control). Orthogonal projection to latent structures analysis correlated bioactive metabolites, identifying key compounds including dihydrokaempferol glucoside, quercetin-3-O-glucuronide, cyanidin-3-O-glucoside, protocatechuic acid glucoside, ergosterol, and bilobalide as potential contributors to α-amylase and α-glucosidase inhibitory activities, which may support antidiabetic potential. These findings suggest that fresh Crimson Seedless grapes possess superior antidiabetic potential, advocating their potential role as a functional food for diabetes management.